2002
DOI: 10.1080/10473289.2002.10470762
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Laser Ablation Mass Spectrometry of Suspended Powders from PM Sources and Its Implications to Receptor Modeling

Abstract: Primary sources of particulate matter (PM) were analyzed by suspending powdered samples into an aerosol laser ablation mass spectrometer (LAMS). PM sources studied included vehicle exhaust particulates, dust from a nonferrous smelter, cement powder, incinerator fly ash, two coal fly ash samples, and two soils. Marker peaks signified certain PM source sectors: construction particles could be distinguished by abundant Ca and Ca compounds, fuel combustion was marked by elemental carbon clusters, and nonferrous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…As shown in Supporting Information Table S2, the strongest associations within the industrial factor were, from weakest to strongest, between Cl, Na, Zn, Pb, Cr, and P. This was similar to the mixing state identified by the ATOFMS and CCSEM/EDX. Furthermore, many of these elements were key markers distinguishing incineration from smelting in the work of Tan et al (21). However, the PIXE factor analysis was unable to identify associations with nitrogen and carbon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Supporting Information Table S2, the strongest associations within the industrial factor were, from weakest to strongest, between Cl, Na, Zn, Pb, Cr, and P. This was similar to the mixing state identified by the ATOFMS and CCSEM/EDX. Furthermore, many of these elements were key markers distinguishing incineration from smelting in the work of Tan et al (21). However, the PIXE factor analysis was unable to identify associations with nitrogen and carbon.…”
Section: Resultsmentioning
confidence: 99%
“…Municipal and hazardous waste incineration have been shown to emit Pb, Zn, and Cl particles (21,(28)(29)(30)(31). For this source, the Cl is primarily from the burning of plastics such as polyvinyl chloride and paper, whereas the Pb and Zn can be produced from a variety of waste materials.…”
Section: Resultsmentioning
confidence: 99%
“…Online measurements of single particles by ATOFMS in an industrial/residential section of Mexico City by Moffet et al (2008a, b) demonstrated that the metal/Cl-containing particles accounted for a large fraction of the fine-mode particles, and the fraction reached 73% in the early morning hours. Other studies have also observed numerous micron-sized Zn/Pb/Cl-containing particles in lead smelter plumes (Ettler et al, 2005), in incinerator fly ash (Tan et al, 2002;Zhang et al, 2009), in mixed urban plumes (Lu et al, 2012), and in haze episodes (Li et al, 2009;Hu et al, 2015). The chloride particles from industrial smoke were often coated by organic matter after aging (see the schematic diagram in Fig.…”
Section: Mixing Of Chlorides In Industrial Smokementioning
confidence: 99%
“…Smaller contributions from Ca, K/Organic, and NO/CH 4 N/Org were found in the positive ion, while H/C 2 /Organics, and Cl/Organics were identified in the negative. These smaller class contributions were expected as well, because work completed earlier on PM sources found that particle types from a standard PM source were chemically diverse [38]. The outlier classes were also small with Ͻ3.9% of the spectra in these classes.…”
Section: Adams Application To a Pm Sourcementioning
confidence: 53%
“…These results showed that the same ADAMS scheme trained and applied to ambient could provide a consistent classification for a PM source. This consistency is important because it has been noted that a classification method for both source and ambient is a necessity for apportioning ambient aerosol LAMS data back to its original source(s) (receptor modeling) [38].…”
Section: Adams Application To a Pm Sourcementioning
confidence: 99%